Lower urinary tract symptoms and sexual dysfunction in men with multiple sclerosis (Clinics, 2019)
OBJECTIVES: To assess the prevalence and interrelationship between lower urinary tract symptoms and sexual dysfunction in men with multiple sclerosis (MS). METHODS: In a cross-sectional study, we evaluated 41 men (mean age 41.1±9.9 years) with MS from February 2011 to March 2013, who were invited to participate irrespective of the presence of lower urinary tract symptoms or sexual dysfunction. Neurological impairment was assessed with the Expanded Disability Status Scale; lower urinary tract symptoms were evaluated with the International Continence Society male short-form questionnaire, and sexual dysfunction was evaluated with the International Index of Erectile Function. All patients underwent transabdominal urinary tract sonography and urine culture. RESULTS: The mean disease duration was 10.5±7.3 years. Neurological evaluation showed a median Expanded Disability Status Scale score of 3 [2-6]. The median International Continence Society male short-form questionnaire score was 17 [10-25]. The median International Index of Erectile Function score was 29 [15-46]. Twentynine patients (74.4%) had sexual dysfunction as defined by an International Index of Erectile Function score o45. Voiding dysfunction and sexual dysfunction increased with the degree of neurological impairment (r=0.02 [0.02 to 0.36] p=0.03 and r=-0.41 [-0.65 to -0.11] p=0.008, respectively). Lower urinary tract symptoms and sexual dysfunction also displayed a significant correlation (r=-0.31 [-0.56 to -0.01] p=0.04). CONCLUSIONS: Most male patients with MS have lower urinary tract symptoms and sexual dysfunction. The severity of the neurological disease is a predictive factor for the occurrence of voiding and sexual dysfunctions.